2013
DOI: 10.5935/abc.20130202
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Strategy in the Three First Months following Bioprosthetic Heart Valve Implantation

Abstract: Heart valve prosthesis unquestionably improve quality of life and survival of patients with severe valvular heart disease, but the need for antithrombotic therapy to prevent thromboembolic complications is a major challenge to clinicians and their patients. Of the articles analyzed, most were retrospective series of cases or historical cohorts obtained from the database. The few published randomized trials showed no statistical power to assess the primary outcome of death or thromboembolic event. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The bioprosthesis emerged last century with the expectation of replacing existing mechanical prosthesis, due to not theoretically requiring permanent oral anticoagulation. Actually, the recommendations of the main international guidelines on antithrombotic therapy after bioprosthesis implantation demonstrate a low level of evidence (Grade C), which may be explained by the lack of randomized trials in this scenario [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioprosthesis emerged last century with the expectation of replacing existing mechanical prosthesis, due to not theoretically requiring permanent oral anticoagulation. Actually, the recommendations of the main international guidelines on antithrombotic therapy after bioprosthesis implantation demonstrate a low level of evidence (Grade C), which may be explained by the lack of randomized trials in this scenario [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, stroke, death and major bleeding occurred only in the first group. All patients in our study have more than a 3-month interval from surgery for recruitment, a period known to have a lower incidence of embolic events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal antithrombotic regimen and its duration after placement of a bioprosthetic device are less clear. Studies have demonstrated that bioprosthetic devices have an increased risk for thromboembolic events during the first three months after the procedure which is less than that associated with mechanical valves [54,55].…”
Section: Anticoagulants In Bioprosthesismentioning
confidence: 99%